Institutional Ethnography: A Marxist-Feminist Approach for the Study of Praxis - Carpenter, Sara; Mojab, Shahrzad (The Canadian Journal for the Study of Adult Education / La revue canadienne pour l’étude de l’éducation des adultes, 2024)
Institutional ethnography (IE) is often seen as a useful tool in the study of organizations and bureaucracy. However, many adaptations of the approach ignore the explicitly historical materialist project embodied in Smith’s conceptualization of “ontological shift” and her assertion that institutional ethnography is a “reinterpretation” of Marx’s epistemology. These adaptations dematerialize and de‑historicize IE as a method of inquiry, thus obscuring Smith’s unique approach to “Marxist feminism” and her particular contributions to the study of capitalist social relations. A similar problem exists in adult education scholarship around questions of consciousness, ideology, and praxis; ideology is reduced to thought content, and consciousness is returned to an idealist position, fragmenting from its dialectical relation to being, or praxis. In this paper, we revisit key formulations with Smith’s sociology to extend their application to the study of praxis in critical adult education.